Current treatment of non-metastatic castration-refractory prostate cancer - Büchler, Tomáš (Klinicka onkologie, 2021)
BACKGROUND: Non-metastatic castration-refractory prostate cancer (nmCRPC) is defined by increasing serum prostate specific antigen (PSA) levels despite androgen deprivation therapy in the absence of metastases on standard imaging methods including CT of the chest, abdomen and pelvis, and bone scan. Patients with nmCRPC and short PSA doubling time (PSAdt) are at high risk of developing early metastatic disease. OBJECTIVES: The objective of this review is to summarize current data on the treatment of nmCRPC. The current data support the efficacy of three novel androgen receptor targeted agents (ARTA), darolutamide, apalutamide and enzalutamide. CONCLUSIONS: The design and eligibility criteria of the three key studies with darolutamide, apalutamide and enzalutamide were similar. Patients were required to have a PSAdt.
Keywords: Prostatic Neoplasms, Castration-Resistant; Androgen Antagonists; Humans; antineoplastic agents; Molecular Targeted Therapy; Antineoplastic Agents; castration-refractory prostate cancer; drug toxicity; androgen antagonists; lidé; zvířata; androgenní receptory; survival; nádory prostaty rezistentní na kastraci; Male; cílená molekulární terapie; Receptors, Androgen; protinádorové látky; Animals; mužské pohlaví; antagonisté androgenů